Factores de Innovación para Fortalecer la Competitividad de Pymes Agroindustriales del Municipio de Dosquebradas Risaralda - Laura Melissa Ceballos Gonzallez (Mundo Fesc)
This research aims to determine the factors of innovation to strengthen competitiveness in SMEs in the agro-industrial sector of the municipality of Dosquebradas. Therefore, a descriptive and interpretive study was carried out with a qualitative approach, applying a data collection instrument, in this case, the survey, conducted with a total of 12 managers as directly responsible for the innovation and development processes within SMEs. Among the main results of this research, it is found that the innovation factor most implemented by SMEs in this sector is product innovation, specifically regarding flavor, texture, changes in packaging and more environmentally friendly containers. On the other hand, the factor that has most challenged companies to implement innovation is innovation in the organization from the creation of a culture of innovation to the implementation of new ways of working, as well as the introduction of technology in all factors.